Matthew 14–28 The Gospel of Matthew, vol 2 - Wilson, Walter T. 1962- (Chicago Wm. B. Eerdmans Publishing Co., 2022)
Intro -- Title Page -- Copyright -- Contents -- List of Abbreviations -- Section Seven: Matthew 14:1-17:27 -- Unit One, Part One (14:1-12) -- Unit One, Part Two (14:13-21) -- Unit One, Part Three (14:22-36) -- Unit One, Part Four (15:1-20) -- Unit One, Part Five (15:21-28) and Part Six (15:29-39) -- Unit One, Part Seven (16:1-12) -- Unit Two, Part One (16:13-28) -- Unit Two, Part Two (17:1-13) -- Unit Two, Part Three (17:14-27) -- Section Eight: Matthew 18:1-35 -- Unit One (18:1-14) -- Unit Two (18:15-22) -- Unit Three (18:23-35) -- Section Nine: Matthew 19:1-23:39 -- Unit One, Part One (19:1-15) -- Unit One, Part Two (19:16-30) -- Unit One, Part Three (20:1-16) -- Unit One, Part Four (20:17-28) -- Unit One, Transition (20:29-34) -- Unit Two, Part One (21:1-11) -- Unit Two, Part Two (21:12-22) -- Unit Two, Part Three (21:23-32) -- Unit Two, Part Four (21:33-46) -- Unit Two, Part Five (22:1-14) -- Unit Two, Part Six (22:15-33) -- Unit Two, Part Seven (22:34-46) -- Unit Three, Part One (23:1-12) -- Unit Three, Part Two (23:13-31) -- Unit Three, Part Three (23:32-39) -- Section Ten: Matthew 24:1-25:46 -- Unit One, Part One (24:1-14) -- Unit One, Part Two (24:15-31) -- Unit Two, Part One (24:32-44) and Part Two-A (24:45-51) -- Unit Two, Part Two-B (25:1-13) -- Unit Two, Part Two-C (25:14-30) -- Unit Three (25:31-46) -- Section Eleven: Matthew 26:1-28:20 -- Unit One, Part One (26:1-16) -- Unit One, Part Two (26:17-29) -- Unit One, Part Three (26:30-56) -- Unit Two, Part One (26:57-75) -- Unit Two, Part Two-A (27:1-10) -- Unit Two, Part Two-B (27:11-31) -- Unit Two, Part Three-A (27:32-44) -- Unit Two, Part Three-B (27:45-56) -- Unit Two, Part Four (27:57-28:10) -- Conclusion (28:11-20) -- Bibliography.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Kommentar